1987
DOI: 10.1007/bf00453481
|View full text |Cite
|
Sign up to set email alerts
|

A comparative experimental study on nerve repair

Abstract: In order to overcome the disadvantages of the classic epi- or perineural nerve suture techniques, attempts have been made to secure nerve endings by a variety of measures, as exemplified by the use of artificial and biological glues. The use of a fibrinogen-thrombin adhesive to seal nerve endings is an easy, time-saving method at surgery and provides excellent coaptation of the severed nerve fascicles with minimal iatrogenic trauma. However, the problem remains of excessive connective tissue proliferation at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
3

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 9 publications
1
21
1
3
Order By: Relevance
“…In terms of the tissue reaction to the cyanoacrylate adhesive, the present results contradict the findings of previous authors 3,4,8 , who found that cyanoacrylate adhesives are cytotoxic and provoke progressive fibrous tissue reaction and constriction near the application areas. In the present study, there was no discernible fibrous thickening, and only a mild degree of foreign body reaction was observed by histologic study surrounding the cyanoacrylates in all specimens.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…In terms of the tissue reaction to the cyanoacrylate adhesive, the present results contradict the findings of previous authors 3,4,8 , who found that cyanoacrylate adhesives are cytotoxic and provoke progressive fibrous tissue reaction and constriction near the application areas. In the present study, there was no discernible fibrous thickening, and only a mild degree of foreign body reaction was observed by histologic study surrounding the cyanoacrylates in all specimens.…”
Section: Discussioncontrasting
confidence: 85%
“…It has been reported that cyanoacrylate adhesives should not be used to bond severed nerves, since these substances penetrate between the two nerve stumps, thereby compressing the regenerating nerve fibers 4,5,8,13 . In order to avoid this problem, we paid particular attention to the overlapping of the epineuriums of the two ends of a severed nerve and applied the minimum amount of adhesive on the surface of the epineurium, just where the epineuriums overlapped.…”
Section: Discussionmentioning
confidence: 99%
“…Small amounts of fibrin glue may be easily applied in order to perform nerve anastomosis. Fibrin glue does not cause foreign body reaction or scar tissue formation, and it also reduces nerve stump manipulation and avoids the use of nylon wires, that remain in close contact with the nerve tissue 2,16,[25][26][27][28][29][30] . In order to check the results attained in the studies about reinnervation dynamics, we can do histologic and functional evaluations.…”
Section: Introductionmentioning
confidence: 99%
“…[83][84][85][86][87][88] Histologic studies have demonstrated increased neuroma lengths at neurorrhaphy sites resulting from interfascicular compared with epineurial repair without statistical difference in myelinated fiber counts between groups in the distal segment 12 months following repair. 89 Use of fibrin adhesive in comparison with microsutures for nerve transection repair and cable graft coaptation has demonstrated equivalent functional and long-term histologic outcomes in the vast majority of randomized controlled studies in animal models while offering the advantage of reduced operating time [90][91][92][93][94][95][96][97][98][99][100][101][102][103] ; however, a minority of studies have demonstrated statistically inferior electrophysiologic outcomes, 104,105 with one demonstrating decreased axon counts 106 in the case in which fibrin glue was used as opposed to nylon microsutures. High-quality human studies comparing coaptation using fibrin glue with conventional epineurial suture repair are lacking; retrospective reviews have demonstrated equivalent functional outcomes for fibrin glue repair of brachial plexus and digital nerves (level IV) 107 and the facial nerve.…”
Section: Neurorrhaphymentioning
confidence: 99%